Safety Compliance and Occupational Accidents: Evidence from Hospital Employees Using Structural Equation Modeling - Kalam Tukiman; Andry Andry; Mohamad Reza Hilmy (Majapahit Journal of Islamic Finance and Management, 2026)
Occupational accidents in hospitals remain a safety issue that impacts the sustainability of services and organizational performance. This study aims to analyse the influence of Safety Leadership, Safety Climate, and Safety Self-Efficacy on Occupational Accidents with Safety Compliance as a mediating variable among employees at Tzu Chi Hospital. The study used a quantitative approach with an analytical survey design. Respondents numbered 296 employees from various work units. Data were collected through a structured questionnaire and analysed using Structural Equation Modelling (SEM) AMOS version 29 to test the direct and indirect effects between variables. The analysis results show that Safety Leadership, Safety Climate, and Safety Self-Efficacy have a significant effect on Safety Compliance. Safety Compliance has a significant effect on Workplace Accidents. In addition, Safety Compliance is proven to mediate the influence of Safety Leadership, Safety Climate, and Safety Self-Efficacy on Workplace Accidents. These findings indicate that strengthening safety leadership, consistent perceptions of safety climate, and employee confidence in safety capabilities play an important role in shaping safe work compliance and reducing the incidence of workplace accidents. This study concludes that occupational accident prevention strategies in hospitals need to focus on strengthening safety leadership behaviour, a supportive safety climate, and increasing employee self-efficacy to encourage sustainable safety compliance.